Asialeyrodes nicobarica sp. nov. (Hemiptera: Aleyrodidae) from the Nicobar Island, located in the Indian part of the Sundaland hotspot, and two new synonymies - Dubey, Anil Kumar (Zootaxa, 2019)
A new whitefly species, Asialeyrodes nicobarica Dubey, sp. nov. found infesting Neolamarckia cadamba (Roxb.) (Rubiaceae) on the Nicobar Island, located in the Indian part of the Sundaland hotspot, is described here. Puparia of the new species differ from all of its congeners in shape, and in having the median tubercles on abdominal segments I–VI, a posteriorly notched vasiform orifice and a broad caudal furrow filled with small linear striations. Asialeyrodes menoni Meganathan and David syn. nov and A. tuberculata Pushpa and Sundararaj syn. nov are synonymised with A. indica Sundararaj and David. Icfrealeyrodes splendens (Meganathan & David) comb. nov. is proposed for Asialeyrodes splendens Meganathan and David. Illustrations include habitus, line drawings, holotype images of the new species and A. tuberculata, and scanning electron microscope photomicrographs. Puparial keys differentiating Asialeyrodes Corbett from allied Indian Aleyrodinae genera and to puparia of species currently included in Asialeyrodes in India are provided. Also, the placement of a non-congeneric species, Rhachisphora spherica Sundararaj and Dubey in Asialeyrodes is discussed.